Analyse Granulometrique et Cartographie des Sediments Superficiels de la Lagune Cotiere au Benin (Afrique de L’Ouest) - Michaël, Tossou Edjrogan; Rodrigue, Adechina Archange; Jéchonias, Hounkpe Bidossèssi; Nelly, Kelome Carine; Aldiouma, Sy Boubou; Tahirou, Diaw Amadou (European Scientific Journal, ESJ, 2019)
The current study is part of the wide-ranging issue related to the sedimentary dynamics of paralic hydro systems. This study aims to characterize the sedimentary cover of the coastal lagoon, one of Benin’s four main water bodies, using the granulometric analysis procedure. Based on shallow sediment samplesâ€™, following 48 transects in the lagoon, a few laboratory processes have been undertaken, including granulometry, statistical calculus acting upon the Folk & Ward textural parameters through Excel and Origin 6.0 software, and also sandy feature mapping, while considering the ArcGIS 10.3 software performance. The grain size indexes of these facies indicate a second or poor-rate classification of medium sands, almost symmetrical, with mesokurtic acuity. The Passega diagram describes a saltation or rolling transport of these sands. The combination of Friedmanâ€™s, Moiolaâ€™s and Weiserâ€™s diagrams reveals fluvial-origin sediments and remobilization from the coastal dune zones flanking the lagoon. At the level of the coastal lagoon, a hydrodynamic zoning is established, characterized by some insubstantial hydro dynamism of the eastern sector, impacted by the influence of the so-called Ouidah lagoon and a relatively strong hydro dynamism of the western sector corresponding to the Grand- Popo lagoon, with a speed ranging between 0.78 to 1.4 m / s towards the bottom and a flow rate of 429 m3 / s, at the Avlo beach station. Ultimately, this study made it possible to underscore the state of hydrodynamic variations observed in the lagoon, notably an opposition between eastern and western sectors, the diversity of sedimentary input sources and the design of the first lithological facies map of this paralic environment, which now stands as a vital tool for its follow-up and monitoring, in the current context of upcoming changes and unremitting alteration. Cette Ã©tude sâ€™inscrit dans la problÃ©matique de la dynamique sÃ©dimentaire des hydrosystÃ¨mes paraliques. Elle se base sur les techniques granulomÃ©triques pour caractÃ©riser les sÃ©diments de la lagune cÃ´tiÃ¨re, lâ€™un des quatre principaux plans dâ€™eau paraliques du BÃ©nin. A partir des prÃ©lÃ¨vements de sÃ©diments superficiels sur 48 transects, des travaux de laboratoire, des calculs de paramÃ¨tres texturaux de Folk & Ward sur Excel et le logiciel Origin 6.0 ainsi que la cartographie des faciÃ¨s via ArcGIS 10.3., ont Ã©tÃ© effectuÃ©s. Les indices granulomÃ©triques de ces faciÃ¨s indiquent un classement mÃ©diocre de sables moyens, presque symÃ©trique, avec une acuitÃ© mÃ©socurtique. Le diagramme de Passega dÃ©crit un transport par saltation ou roulement de ces sables. La combinaison des diagrammes de Friedman, Moiola et Weiser montre des sÃ©diments dâ€™origine fluviatile et ceux remobilisÃ©s Ã partir des dunes cÃ´tiÃ¨res adjacentes Ã la lagune. Un zonage hydrodynamique est Ã©galement notÃ©, caractÃ©risÃ© par un hydrodynamisme faible du secteur oriental ou lagune de Ouidah et un hydrodynamisme relativement fort du secteur occidental ou lagune de Grand-Popo, avec une vitesse de lâ€™ordre de 0,78 Ã 1,4 m/s vers le fond et un dÃ©bit de 429 m3 /s, Ã la station de Avlo Plage. En dÃ©finitive, ce papier fait ressortir lâ€™Ã©tat de variations hydrodynamiques de la lagune, notamment une opposition entre secteurs oriental et occidental, la diversitÃ© des sources dâ€™apports sÃ©dimentaires et la rÃ©alisation de la premiÃ¨re carte des lithofaciÃ¨s de cet environnement aquatique, outil indispensable Ã son suivi face Ã des changements futurs et Ã un contexte en mutation perpÃ©tuelle.